Post-occlusive reactive hyperaemia (POHR) in systemic sclerosis: very early disease (VEDOSS) represents a separate entity compared to established disease. (2nd September 2016) - Della Rossa, A; D'Ascanio, A; Barsotti, S; Stagnaro, C; Mosca, M
Abstract : Objectives : Vascular involvement is a key feature of systemic sclerosis (SSc). Vascular changes are central to the pathogenesis of the disease and the assessment of vascular involvement has a prognostic value. This assessment therefore has a pivotal role in the management of SSc patients. The aim of our study was to evaluate post-occlusive reactive hyperaemia (PORH) in consecutive SSc patients and to test whether a PORH test might be a useful tool for the early diagnosis of SSc. Method : Between April 2011 and April 2015, 60 consecutive SSc patients (mean age 56 ± 15 years, females:males = 18:1) were enrolled in the study. The patients were divided into those with full-blown SSc (n = 50) and those with very early diagnosis of SSc (VEDOSS) (n = 10) according to the literature. Laser speckle contrast analysis (LASCA) was used to assess PORH. Results : A statistically significant difference was detected in the post-ischaemic hyperaemic peak flow between VEDOSS and established SSc (424% vs. 137%, p = 0.0011). PORH peak flow decreased according to the capillaroscopic pattern (early = 419%, active = 163%, late = 145%, p = 0.0027). Moreover, a correlation between capillary density and peak flow was revealed (rho = 0.33, p < 0.01). Conclusions : These data show a different pattern of vascular involvement in VEDOSS compared to established disease that mirrors capillaroscopic changes. Functional features of very early and established disease seem to be the physiological counterpart of abnormalities detected by capillaroscopy. The POHR test might be a useful aid for further characterization of vascular involvement in SSc. In particular, blunted POHR might prove a tool to separate pre-clinical from full-blown SSc.